Demographic, economic and psychological determinants of remittance behavior among Cebuano domestic helpers in Hong Kong - Talam, Anna Marie P. (2001)
The study examines the relationships between the amount of remittance (in portion of income) of temporary migrants in a host country, the Cebuano domestic helpers (DH) in Hong Kong, and each of the selected demographic, economic, and psychological variables. Data for this study comes from a survey questionnaire fielded in three district areas using the three-stage with quota sampling technique. Data were analyzed using chi square test of independence (p<0.05).
Keywords: Filipino foreign workers -- Hong Kong